2010
DOI: 10.1042/bj20091091
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide triggers mammary gland involution after weaning: remodelling is delayed but not impaired in mice lacking inducible nitric oxide synthase

Abstract: During mammary gland involution, different signals are required for apoptosis and tissue remodelling. To explore the role of NO in the involution of mammary tissue after lactation, NOS2 (inducible nitric oxide synthase)-KO (knockout) mice were used. No apparent differences were observed between NOS2-KO and WT (wild-type) animals during pregnancy and lactation. However, upon cessation of lactation, a notable delay in involution was observed, compared with WT mice. NOS2-KO mice showed increased phosphorylation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 45 publications
1
29
0
Order By: Relevance
“…[3][4][5][6] NF-kB regulates the expression of a large number of genes involved in multiple biological processes, including apoptosis. We have shown that both Capn1 and 2 are regulated by NF-kB during mammary gland involution (Figure 1a).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[3][4][5][6] NF-kB regulates the expression of a large number of genes involved in multiple biological processes, including apoptosis. We have shown that both Capn1 and 2 are regulated by NF-kB during mammary gland involution (Figure 1a).…”
Section: Discussionmentioning
confidence: 99%
“…Caspase-3 activity was measured in mammary tissue lysates using the 'Caspase-3/CPP32 Colorimetric Assay Kit' (#K106, BioVision, Mountain View, CA, USA) as previously described. 5 Statistics. Data are presented as means±S.E.M.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations